Microencapsulation of fig seed oil rich in polyunsaturated fatty acids by spray drying - Icyer, Necattin Cihat; Toker, Omer Said; Karasu, Salih; Tornuk, Fatih; Kahyaoglu, Talip; Arici, Muhammet (SPRINGER, 2017)
Fig oil is a nutritious vegetable based oil type which is rich in polyunsaturated fatty acids. In the present study, several attempts have been made to produce encapsulated oil with maximum efficiency. In the first step, the effect of feed concentration was observed at 140, 150 and 160 degrees C and 20 % dry matter was selected. In the second step, distribution of gum arabic (GA) and maltodextrin (MD) as a wall material was determined at different temperature levels (140, 150, 160, 170 and 180 degrees C), and optimum MD/GA ratio and temperature were found to be 8/1 and 150 degrees C, respectively. In the next step, impact of wall material/fig oil ratio on the encapsulation efficiency was investigated and it was determined to be 3.0. According to the results, optimum encapsulation ratio of MD/GA/oil and temperature were 8/1/3 and 150 degrees C, respectively. The physicochemical properties; particle size, peroxide value, dry matter content, and encapsulation efficiency of the oil encapsulated under this condition were determined. Water content and water solubility of the powder was determined as 2.875 and 97.85 %, respectively. At the optimum conditions particle of the fig oils showed smooth surface, non-homogeneous and spherical shape, and size of the most of the particles ranged between 8 and 40 mu m.
Keywords: Fig oil; Encapsulation; Wall material; Drying temperature; Polyunsaturated fatty acid; FISH-OIL; OXIDATIVE STABILITY; ENCAPSULATION EFFICIENCY; WALL MATERIALS; MALTODEXTRIN; RETENTION; EMULSIONS; FRUITS; IMPACT; Food Science & Technology